1971
DOI: 10.1128/jvi.7.5.646-650.1971
|View full text |Cite
|
Sign up to set email alerts
|

Transfection of Escherichia coli Spheroplasts I. General Facilitation of Double-Stranded Deoxyribonucleic Acid Infectivity by Protamine Sulfate

Abstract: The addition of 25 ,ug of protamine sulfate per ml to lysozyme-ethylenediaminetetraacetic acid spheroplasts of Escherichia coli stimulates transfection not only for Ti phage deoxyribonucleic acid (DNA; Hotz and Mauser, 1969) but also for the following phage DNA species: lambda, 10,000-fold to an efficiency of 10-3 infective centers per DNA molecule; 4X174 replicative form, 300-fold to an efficiency of 5 x 10-2; fd replicative form, 300-fold to 10-6; T7, 300-fold to 3 x 10-1. Three native phage DNA species were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
0

Year Published

1972
1972
1977
1977

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…It was shown that transfecting native and denatured T7 DNA is biologically inactivated by the in vivo activity of the recBC DNase. Native T7 DNA is more severely affected, which confirms earlier findings (2) and is in agreement with the notion that linear duplex DNA is efficiently attacked by the recBC DNase in vivo (3,24,29,33). This also could be the reason for the T7 function that inactivates the recBC DNase after phage infection (32).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It was shown that transfecting native and denatured T7 DNA is biologically inactivated by the in vivo activity of the recBC DNase. Native T7 DNA is more severely affected, which confirms earlier findings (2) and is in agreement with the notion that linear duplex DNA is efficiently attacked by the recBC DNase in vivo (3,24,29,33). This also could be the reason for the T7 function that inactivates the recBC DNase after phage infection (32).…”
Section: Discussionsupporting
confidence: 91%
“…Besides these applications of transfection, it has also been shown that transfection may serve to test the presence of certain cellular enzymes, in particular the recBC DNase (9,41). The presence of this enzyme in the recipient cells decreases drastically the biological activity of linear duplex DNA (3,23,29,33).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results also further support the evidence that mycRNA has a double-stranded structure because protamine sulfate combined with it to form a heavy precipitate and decreased its biological activity. Protamine sulfate does not combine with single-stranded nucleic acids (6). In addition, streptomycin sulfate does not bind single-stranded yeast RNA or soluble RNA (1), but it did bind with mycRNA to form a heavy precipitate which was easily sedimented by low-speed centrifugation.…”
Section: Discussionmentioning
confidence: 99%
“…The polybasic amines, because of their basic charge, will bind with the acidic groups of certain haptens and nucleotides to form relatively stable complexes which then become capable of inducing antibody formation to the hapten or nucleotide. Some investigators (2,3,32) feel that the poly-evidence might be obtained concerning whether the mycRNA exists as a double helical structure, as our previous work has suggested (38), since some of the polybasic amines complex more readily with double-stranded nucleic acids (1,6). MATERIALS AND METHODS Polybasic amines.…”
mentioning
confidence: 99%